2012
DOI: 10.1155/2012/506868
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain, Metabolic Syndrome, and Breast Cancer Recurrence: Are Dietary Recommendations Supported by the Data?

Abstract: Metabolic syndrome, which can include weight gain and central obesity, elevated serum insulin and glucose, and insulin resistance, has been strongly associated with breast cancer recurrence and worse outcomes after treatment. Epidemiologic and prospective data do not show conclusive evidence as to which dietary factors may be responsible for these results. Current strategies employ low-fat diets which emphasize supplementing calories with increased intake of fruit, grain, and vegetable carbohydrate sources. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 80 publications
2
61
3
7
Order By: Relevance
“…TNF-α also plays a role in angiogenesis (Cereda et al, 2012;Gómez Flores-Ramos et al, 2013) by inducing the expression of adhesion molecules and facilitating the invasion of metastatic tumor cells (Gómez FloresRamos et al, 2013;Zelová and Hošek, 2013). In vitro and in vivo studies have shown that high levels of TNF-α are associated with poor prognoses in cancer patients due to its tumorigenic effects (Champ et al, 2012;Gómez Flores-Ramos et al, 2013). Several studies have demonstrated a significant association between cytokine levels and increased CRC risk (Fan et al, 2011) or severity (Stanilov et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α also plays a role in angiogenesis (Cereda et al, 2012;Gómez Flores-Ramos et al, 2013) by inducing the expression of adhesion molecules and facilitating the invasion of metastatic tumor cells (Gómez FloresRamos et al, 2013;Zelová and Hošek, 2013). In vitro and in vivo studies have shown that high levels of TNF-α are associated with poor prognoses in cancer patients due to its tumorigenic effects (Champ et al, 2012;Gómez Flores-Ramos et al, 2013). Several studies have demonstrated a significant association between cytokine levels and increased CRC risk (Fan et al, 2011) or severity (Stanilov et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α has a receptor on tumor cells that stimulates activation and prolonged expression of the JUN oncogene; participates in apoptosis; stimulates the hydrolysis of sphingomyelin, ceramide, and phosphorylcholine; and induces the production of reactive oxygen species (Cereda et al, 2012). In vitro and in vivo experiments have shown the tumorigenic effects of TNF-α, and it has been associated with elevated plasma levels of TNF-α in cancer patients with a poor prognosis (Champ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TNF-α induces the expression of adhesion molecules, facilitating the invasion of metastatic tumor cells (Champ et al, 2012). Multiple studies have found a significant association between this cytokine and increased risk for BC (Fang et al, 2010;Shen et al, 2011), and an increase in the severity of the disease (Azmy et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…51 Metabolic syndrome, IR and hyperglycaemia are all associated with breast cancer recurrence, which has many oncologists and dietitians calling current dietary guidelines into question. 52 AD is now frequently referred to as 'diabetes of the brain' or 'type 3 diabetes', bringing immediate attention to the role of insulin dysregulation and impaired blood glucose. 53,54 A wealth of research implicates brain IR in the pathology and progression of this condition.…”
Section: The Scope Of the Problemmentioning
confidence: 99%